Nutrient film technique systems for coriander production: A comparison of aquaponics and hydroponics in UAE - Ahmed Al Jenaid; Mohamed El Mahi; Abdulla Saeed Bathaqili; Abdallah Khamas Alalawi; Chythra Somanathan Nair; Drishya Nishanth; Radhakrishnan Subramanian; Ramya Manoharan; Abdul Jaleel (PLoS ONE, 2026)
As global populations rise, the need for sustainable agricultural practices becomes increasingly urgent, especially in regions facing water scarcity and harsh environmental conditions. Traditional farming methods are often unsuitable for arid areas, leading to the exploration of alternative techniques like hydroponics and aquaponics. These soilless systems offer efficient water use and nutrient management, making them ideal for regions where conventional farming is challenging. This study compares the efficiency of Nutrient Film Technique (NFT) systems in aquaponics and hydroponics for coriander production. Both systems provide controlled environments for plant growth but differ in their nutrient sources—aquaponics integrates fish farming, while hydroponics relies on synthetic nutrient solutions. The aquaponic system incorporated Nile Tilapia ( Oreochromis niloticus ), which provided nutrients through fish waste, while the hydroponic system used a commercially prepared nutrient solution. Coriander, as a leafy herb, can perform well in aquaponic systems because nitrogen, phosphorus, and some micronutrients from fish waste support growth. Nutrient availability depends on fish stocking density, feed quality, and system maturity, with well-fed fish and a mature system enhancing nutrient release. However, long-term or high-yield production may still require supplementation of elements like calcium, magnesium, or iron, as fish effluent alone may not fully meet crop nutrient demands. Key parameters like plant growth (total weight, shoot length, root length), water quality (pH, nitrate, phosphate), and biochemical attributes (chlorophyll, phenol content, antioxidant activity) were assessed. Results indicated that the aquaponics system outperformed hydroponics in plant growth parameters, with coriander grown in aquaponics showing greater total weight, shoot length, and root length. Aquaponics-grown plants also exhibited higher chlorophyll content and antioxidant activity, suggesting improved photosynthesis and nutritional quality. While hydroponic plants had slightly higher phenolic content, aquaponics facilitated better mineral accumulation, particularly for calcium, magnesium, phosphorus, and zinc. The findings demonstrate that aquaponics offers a more sustainable and efficient approach to coriander production, providing higher yield and superior nutritional quality compared to hydroponics. This highlights the potential of aquaponics for enhancing food security in water-scarce regions.